Проектне управління, як основа енергозбереження у житлово-комунальному господарстві - Бубенко, Павло Трохимович; Бубенко, Олексій Павлович (НТУ "ХПІ", 2017)
Розглянуто науковий підхід до проблематики енергозбереження у ЖКГ з позицій програмно-цільового управління, коли на відміну від існуючої практики вирішення завдань енергозбереження, цей процес здійснюється на основі аналізу і співставлення витрат і втрат ресурсів по кожному енергозбережному об‘єкту, а сам процес енергозбереження базується на положеннях теорії проектного управління. Доведено необхідність обов‘язкового врахування індустрії будівництва житла з підгалузями ЖКГ у процесі реалізації стратегії енергозбереження.

Considered a scientific approach to energy conservation issues in the housing from the standpoint of program-oriented management, when in contrast to the current practice solutions of energy saving tasks, the process is carried out based on the analysis and comparison of the costs and resource losses for each energy-saving project, and the energy-saving process is based on the provisions of the theory project management. The necessity of mandatory registration of housing construction industry sub-sectors with the utilities in the process of implementing energy-saving strategies. Proposed key areas of energy efficiency of existing and new buildings, formed components selection, programming and planning of energy saving activities at the strategic, tactical and operational levels. We studied the organizational and structural relationship of the construction sector and sub-sectors of housing and communal services in the implementation of energy-saving strategies. We prove the advantages of using the network form of organizational and economic support implementation of energy saving projects.
Project management as the basis for energy saving in housing and utilities sector
Keywords: енергоресурси; енергозбереження; проектне управління; будівельна галузь; житло; energy; saving; project management; construction industry; housing